Experimental and computational study on the effects of high pressure on the crystal structure of boron nitrilotriacetate - Montisci, Fabio; Ernst, Michelle; Macchi, Piero (Crystal growth & design, 2023)
Herein, we report the structural changes occurring to the molecule of boron nitrilotriacetate and its interactions when the crystal is under compression. A special focus is on the intermolecular interactions involving the carbonyl groups. In fact, these short-range contacts may anticipate cooperative addition reactions that could eventually lead to a polymer. However, X-ray diffraction experiments do not evidence any polymerization at least up to 16 GPa, due to competing interactions. In this work, we use and illustrate several theoretical tools to investigate the variable nature of the intermolecular interactions and their changes upon compression.
Gesehen am 17.05.2023